Development of Karnal bunt resistant bread wheat doubled haploid lines - Nagarajan, Ragupathy; Sharma, Achla; Kashyap, Lenika; Srivastva, Puja; Sharma, Indu; Bains, Navtej Singh (Journal of Cereal Research, 2012)
A set of 151 doubled haploid lines were generated from crosses between elite bread wheat lines and Karnal buntresistance donors using wheat x maize system. Donor alleles of three markers; Xgwm99 (1AL), Xwmc 445 (5AL) and Xgwm340 (3BL) known to be associated with KB resistance were run on the DH lines. After preliminary screening for resistance and plant type, 24 lines along with four checks were chosen for yield testing and confirmatory screening against Karnal bunt. Seventeen of the doubled haploid lines showed Karnal Bunt score of less than 5% whereas check varieties, PBW 343 (18.3%), PBW 550 (20.4%), PBW 621 (20.1%) and HD 2967 (13.6%) showed higher levels of Karnal Bunt infection. A Karnal Bunt score of less than 1% was observed in three doubled haploid lines, namely BWL 0009 (0.60%), BWL 0001 (0.67%) and BW 9996 (0.87%). Two doubled haploid lines (BW 9986 and BW 9991) combining Karnal Bunt resistance (< 2%) and high yield were identified and promoted to multilocation evaluation.